EVALUASI IMPLEMENTASI TAMBAHAN PENGHASILAN PEGAWAI NEGERI SIPIL - Ihsan, Nur (Jurnal Ilmu Administrasi Negara, 2017)
Abstract: Evaluation of the Implementation of Civil Servants Income Supplement. This study aims to evaluate the implementation of policies and look at the factors that influence policy implementation Income Supplement Civil Servants. The method used is descriptive explanatory with a qualitative approach. The technique of collecting data using interviews, direct observation, documentation. Determination of informants pusposive engineering research with sampling and snowball sampling. The process of data analysis with interactive analysis. Implementation of additional policies have been implemented employee income well as payments are made on a regular basis each month, in accordance with the level of discipline and work performance of employees.